Effects of low-intensity DC magnetic field on the freezing process of aqueous solution and beef - WANG,Yiran (2022)
Abstracts In this paper, experiments were conducted to study the effect of weak magnetic fields on the freezing process of deionized water and physiological normal saline. The results show that different magnetic field strengths have different effects on aqueous solutions. Only a certain strength of the magnetic field will have a positive effect on the freezing process of the aqueous solution, and generally speaking, the effect of the magnetic field on the normal saline is better than that of deionized water. When the magnetic field strength is 150G, the magnetic field has a positive effect on the supercooling degree and the supercooling time of the saline. In the beef freezing experiment, it was found that the magnetic field can not only promote the freezing process of beef but also inhibit the freezing process. Whether a fan is added will also affect the freezing effect of the magnetic field on the beef.The magnetic field strength of 40G and 50G has a significant promotion effect on the freezing process of beef, while the magnetic field strength of 100G~150G has a significant inhibitory effect.